The roles of long noncoding RNA-mediated macrophage polarization in respiratory diseases - Qiao, Xin; Ding, Yuxiao; Wu, Dasen; Zhang, Anle; Yin, Yan; Wang, Qiuyue; Wang, Wei; Kang, Jian (Frontiers in Immunology, 2023)
Macrophages play an essential role in maintaining the normal function of the innate and adaptive immune responses during host defence. Macrophages acquire diverse functional phenotypes in response to various microenvironmental stimuli, and are mainly classified into classically activated macrophages (M1) and alternatively activated macrophages (M2). Macrophage polarization participates in the inflammatory, fibrotic, and oncogenic processes of diverse respiratory diseases by changing phenotype and function. In recent decades, with the advent of broad-range profiling methods such as microarrays and next-generation sequencing, the discovery of RNA transcripts that do not encode proteins termed “noncoding RNAs (ncRNAs)” has become more easily accessible. As one major member of the regulatory ncRNA family, long noncoding RNAs (lncRNAs, transcripts >200 nucleotides) participate in multiple pathophysiological processes, including cell proliferation, differentiation, and apoptosis, and vary with different stimulants and cell types. Emerging evidence suggests that lncRNAs account for the regulation of macrophage polarization and subsequent effects on respiratory diseases. In this review, we summarize the current published literature from the PubMed database concerning lncRNAs relevant to macrophage polarization and the underlying molecular mechanisms during the occurrence and development of respiratory diseases. These differentially expressed lncRNAs are expected to be biomarkers and targets for the therapeutic regulation of macrophage polarization during disease development.